Phylogenetic Diversity and Susceptibility of Candida Species from Women using Contraceptive Devices in Central Nigeria. (March 2022) - Lillian, A.; Chuku, A.; Joseph, N.; Ajide, B.; Reuben, R.; Akwashiki, O.
Abstract : Purpose: The use of contraceptive devices predisposes women to vulvovaginal candidiasis globally. Despite the high incidence of vulvovaginal candidiasis and antifungal resistance to azoles, the genetic diversity and resistance pattern among contraceptive users in Nigeria is poorly investigated. This study therefore sought to characterize and determine the phylogenetic breadth of Candida spp. as well as their resistance to antifungal agents from women using contraceptive devices in central Nigeria. Methods & Materials: This study recruited 1, 600 women using contraceptive devices that visited gynaecology and obstetrics clinics in central Nigeria between August, 2018 to February, 2020. Candida spp. were isolated and characterized using conventional methods and the sequencing of the internal transcribed spacer (ITS) region of the ribosomal DNA (rDNA). Bayesian phylogenetic analysis was used to characterize the diversity of Candida spp. Agar well diffusion technique and primer-specific PCR were used for the determination of antifungal susceptibility profiles and the presence of resistant genes. Results: Five Candida spp. were identified from 710 contraceptive users with vulvovaginal candidiasis. Although Candida albicans was the predominant (43.23%) Candida spp. isolated, other non-albicans Candida spp. included C. glabrata (19.01%) C. tropicalis (15.77%) C. parapsilosis (8.87%) and C. akabanensis (13.09%) respectively. The molecular characterization of the different Candida spp. and their phylogenetic relationships were confirmed using the Bayesian analysis. All the Candida spp. revealed varying degrees of susceptibilities to voriconazole, fluconazole and nystatin. However, C. albicans showed 29.0% resistance to fluconazole, C. tropicalis showed 46.0% and 14.0% resistance to nystatin and voriconazole while C. akabanensis showed 100% resistance to voriconazole and fluconazole, respectively. Kruskal-Wallis Chi-square test using 'R' (Version 3.2.2) showed nystatin as the most effective antifungal agent (Kruskal-Wallis χ 2 = 786.03, df = 2, P < 0.001) against Candida spp. Also, resistant gene Erg11 was identified in all the Candida spp. resistant to the antifungal agents tested. Conclusion: Women using contraceptive devices in central Nigeria harbour phylogenetically diverse Candida spp. including C. akabanensis an uncommon cause of vulvovaginal candidiasis. Out of these Candida spp. C. albicans, C. tropicalis and C. akabanensis are notable for multidrug drug resistance as well as harbouring resistant gene Erg11 .